As artes na educação integral: uma apreciação histórico-crítica - Duarte, Newton [UNESP]; Ferreira, Nathalia Botura de Paula (My University, 2011)
The present work aims to draw some reflections on the role of art in integral education, particularly of art as a school subject. The paper focuses on the contribution of art to the development the individual and the higher psychological functions. The arguments presented here are based on the studies on art made by Lev Vygotsky and Georg Lukács and also on the educational studies made by Dermeval Saviani. We expect to contribute to the defense of the necessity of an integral education in which art, integrated with science and philosophy, opposes itself to the predominantly fetishistic and unilateral character of the activities that constitutes the life in the contemporary capitalist society.

O trabalho que ora se apresenta presta-se a traçar algumas reflexões acerca do papel da arte na educação integral, mais precisamente da arte como conteúdo escolar. O artigo concentra-se na contribuição que a arte pode dar ao desenvolvimento do indivíduo e de suas funções psicológicas superiores. Os argumentos desenvolvidos no artigo fundamentam-se em estudos sobre a arte realizados por Lev Vigotski e por Georg Lukács, bem como em estudos educacionais realizados por Dermeval Saviani. Espera-se contribuir para a defesa da necessidade de uma educação integral na qual a arte, juntamente com a ciência e a filosofia, se oponha ao caráter predominante fetichista e unilateral das atividades que constituem a vida na sociedade capitalista contemporânea.
Art and integral education: an historical-critical analysis
Keywords: Integral education; Art; Lev Vygotsky; Georg Lukács; Educação integral; Arte; Lev Vigotski; Georg Lukács